Teleradiology: technology and practice...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston, TX, May 6-9, 1999 - Frey GD; Spicer KM (Journal of Digital Imaging)
Teleradiology increases the ability of radiologists to provide service to remote and underserved locations as well as coverage at times when direct reading of images is not possible. Good practices for teleradiology are described in the American College of Radiology (ACR) teleradiology standard. Teleradiology equipment is converging with picture archiving and communications systems (PACS) equipment so that diagnostic interpretation from remote locations is possible. Image capture can be directly from digital modalities or by film scanner. Transmission speed is still an issue. High transmission speeds were difficult to achieve but recent improvements may increase speeds and decrease costs. Copyright (c) 1999 by W.B. Saunders Company